2004
DOI: 10.1002/food.200300338
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vitamin B6 supplementation on polyunsaturated fatty acids concentration in serum and liver of rats fed a diet restricted in protein

Abstract: The influence of vitamin B6 on fatty acids content in serum and liver of rats receiving low protein diets was studied. Addition of B6 decreased linoleic acid (LA) and increased alpha-linolenic acid (ALA) and docosahexaenoic acid (DHA) in serum of rats fed a protein-deficient diet (9% energy from proteins) for 3 months. Further restriction of dietary protein (4.5% of energy from protein) caused an increase of the DHA concentration and sum of polyunsaturated fatty acids (PUFAs). In the liver of undernourished ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…Witten and Holman [13] observed a decrease of arachidonic acid concentration in tissues of rats fed B 6 deficient diet and Goswami and Coniglio [1] found that deficient of vitamin B 6 simultaneous decreased of LA and increased of another PUFAs concentration in rat's testis. In malnutrition of rats obtained by restriction of the adequate diet consumption up to 50% and 30% daily consumption the vitamin B 6 addition caused significant changes of PUFAs in blood serum and liver [5].…”
Section: Resultsmentioning
confidence: 98%
“…Witten and Holman [13] observed a decrease of arachidonic acid concentration in tissues of rats fed B 6 deficient diet and Goswami and Coniglio [1] found that deficient of vitamin B 6 simultaneous decreased of LA and increased of another PUFAs concentration in rat's testis. In malnutrition of rats obtained by restriction of the adequate diet consumption up to 50% and 30% daily consumption the vitamin B 6 addition caused significant changes of PUFAs in blood serum and liver [5].…”
Section: Resultsmentioning
confidence: 98%
“…The PDXDC1 protein, a vitamin B6-dependent decarboxylase, is expressed preferentially in the intestine [44], but its function is not known. Animal studies support an influence of dietary vitamin B6 (pyridoxal) on serum and liver levels of ALA and other PUFAs [45], [46], which has been interpreted as an effect on desaturase enzymes activity. The association of PDXDC1 with ALA, if confirmed in other studies, raises the possibility of another vitamin B6-dependent protein affecting ALA, for example through involvement in intestinal ALA absorption.…”
Section: Discussionmentioning
confidence: 97%
“…Also in rats fed PR diet during pregnancy, alteration of membrane fatty acid content and composition in the offspring were noticed (Burdge et al., 2003). In a previous experiment, we have shown that addition of vitamin B 6 to low protein diet caused an increase in PUFAs particularly alpha‐linolenic and docosahexoenoic acid in serum of rats (Bertrandt et al., 2004). This vitamin in the form of pirydoxal phosphate participates in lipid metabolism, mainly in PUFAs desaturation (Bordoni et al., 1998).…”
Section: Discussionmentioning
confidence: 99%